Genome-wide identification of actin-depolymerizing factor family genes in melon (Cucumis melo L.) and CmADF1 plays an important role in low temperature tolerance - Lv, Yanling; Liu, Shihang; Zhang, Jiawang; Cheng, Jianing; Wang, Jinshu; Wang, Lina; Li, Mingyang; Wang, Lu; Bi, Shuangtian; Liu, Wei; Zhang, Lili; Liu, Shilei; et al. (Frontiers in Plant Science, 2024)
Actin depolymerizing factors (ADFs), as the important actin-binding proteins (ABPs) with depolymerizing/severing actin filaments, play a critical role in plant growth and development, and in response to biotic and abiotic stresses. However, the information and function of the ADF family in melon remains unclear. In this study, 9 melon ADF genes (CmADFs) were identified, distributed in 4 subfamilies, and located on 6 chromosomes respectively. Promoter analysis revealed that the CmADFs contain a large number of cis-acting elements related to hormones and stresses. The similarity of CmADFs with their Arabidopsis homologue AtADFs in sequence, structure, important sites and tissue expression confirms that ADFs are conserved. Gene expression analysis showed that CmADFs responded to low and high temperature stresses, as well as ABA and SA signals. In particular, CmADF1 was significantly up-regulated under above all stress and hormone treatments, indicating that CmADF1 plays a key role in stress and hormone signaling responses, so CmADF1 is selected to further study the mechanism in low temperature tolerance. Under low temperature, the stable genetic overexpression of CmADF1 in Arabidopsis promoted seedlings growth, improved their low temperature tolerance, and caused instability of their actin filaments. Consistently, virus-induced gene silencing (VIGS) of CmADF1 in oriental melon plants showed increased sensitivity to low temperature stress. Overall, our findings contribute to understanding the foundational information and function of CmADFs, and demonstrate the positive regulatory role of CmADF1 on plant resistance to low temperature.